PEMAHAMAN KONSEP PENDIDIKAN MULTIKULTURAL DALAM PERSPEKTIF UU SISDIKNAS - Dwi Intan Budiana; Dian Nur Azizah; Ahmad Mansur (STKIP Subang, 2026)
Diversity, encompassing cultural, ethnic, religious, and linguistic aspects, is an integral part of Indonesian society. This reality calls for an education system that can embrace differences while fostering mutual respect. In the National on the National Education System, this principle is reflected in the objectives of national education, which are aimed at shaping individuals who uphold the values of democracy and respect diversity. This study aims to examine understandings of multicultural education within the framework of the National Education System Law as well as its impact on the implementation of education. The method applied in this research is a qualitative approach with a library study type. Data collection is conducted through the examination of various written sources, such as legislation, reference books, and scientific journals obtained via Google Scholar. The sampling technique in this study was designed to identify and select relevant sources published within the last decade. The results of the study indicate that multicultural education in the National Education System Law emphasizes the importance of recognizing and respecting diversity as part of the nation’s identity. However, understanding of this concept in educational practice remains insufficient, particularly regarding its implementation in the curriculum and the learning process. Therefore, targeted and sustained efforts are needed to improve the learning process. Therefore, there is a need for directed and continuous efforts to improve both understanding and the implementation of multicultural education in educational settings.